Žalec sredi 19. stoletja - Baš, Angelos (Etnolog. Nova vrsta (Ljubljana), 2007)
The article publishes the principal data on Zalec and its immediate environs from 1843č they are taken from the Topographie des Herzogtums Steiermark by Georg Göth and provide detailed information on life in the Duchy of Styria in the first half of the 19th century. The topography lists the main data on the houses, population, and population groups. It contains data on the local agriculture, stockbreeding and crafts, in particular on smiths and the parts they made for carts, and on rural trade. It mentions the Catholic and the Protestant faiths and pilgrimages to Petrovee. Göth lists all the types of church land and the peasants living on it, the conversion of corvée into moneyand the simultaneous continuation of corvée (30 days a year). Further data describe the municipalityćs real estate, poorhouse, hospital, school and its premises, number of pupils, and their background. During the constitutional period (from 1861 onwards) life in Zalec and its environs considerably developed, especially in education, economy, politics, and the health service.
Keywords: Slovenci; Slovenes; Štajersko; Žalec; poljedelstvo; živinoreja; animal husbandry; trade; trgovina; obrt; 19. stoletje; 19th century; Göthova topografija